The financial crisis: What have macroeconomists learnt? - Jagjit S. Chadha (University of Kent, School of Economics, 2010)
I outline a simple roadmap for work in micro-founded models. Rather than abandoning the route to further micro-foundations and returning to ad hoc economics, the techniques we have used over the past two decades to develop micro-founded business cycle models will allow us to develop models with meaningful financial frictions and thus address once again the question of monetary and fiscal policies with active rather then passive financial sectors. Macroeconomics and finance are likely to remain bound together.
Keywords: E42; E52; E58; 330; future of macroeconomics; DSGE models; crisis